DETERMINATION OF COMPETENCE, WORK CULTURE, AND ORGANIZATIONAL SUPPORT TO PERFORMANCE THROUGH WORK SATISFACTION - Ali, Muhamad; Wibisono, Chablullah; Indrayani; Yanti, Sri; Dewi, Nolla Puspita (International Journal of Psychosocial Rehabilitation, 2020)
The increase in demand for air transportation services to and from Batam City must be balanced with an increase in airport facilities and infrastructure, both in the interests of aircraft and the interests of passengers and goods (payload). The improvement of facilities can be in the form of an increase in aircraft capacity, or an increase in infrastructure in the form of the development of the airside (landside) and the landside (landside). Performance appraisal is an employee performance control process that is evaluated based on certain standards. Performance appraisals are carried out effectively to direct employee behavior in order to produce high-quality services. Besides, performance appraisals are also carried out to motivate employees to carry out their duties and realize company goals. Many factors can affect performance, including motivation, Competence, leadership, work discipline, work culture, communication, commitment, position, quality of work-life, training, compensation, work environment, organizational support, and many others. The population in this study were all employees of the Avsek and Pkp-pk units. They served at the Hang Nadim Airport in Batam City, amounting to 325 people, next calculated by the Slovin formula obtained 150 respondents. Determination is the Squared Multiple Correlation value for Work Kepleness times 100% = 0.483 x 100% = 48, 3%. Thus, it can be stated that changes in job satisfaction are influenced by Competence, Work Culture, and Organizational Support by 48.3%.